Supplier assessment: a commitment to food safety - Compeau, Elizabeth (Kansas State University, 2013)
In the development of a hypothetical new food product (Beta Buzz) a company must have a thorough understanding of the associated food safety risks, and control factors needed to protect their consumers and their brand. The company must understand each of the suppliers, and take a proactive approach in determining the supplier requirements. It is critical that manufacturing risks be controlled and/or reduced through a combination of internal program compliance, government regulations, third party audit compliance, and/or customer audits and expectations with a focus on ingredients, the finished product and the manufacturing process itself. Food consumers have a right to safe food; the industry, as well as the government, has a responsibility to ensure consumers receive safe food.
Keywords: Food safety audit; GFSI; Food Science (0359)